A minimally designed soft crawling robot for robust locomotion in unstructured pipes. (1st September 2022) - Yu, Wenkai; Li, Xin; Chen, Dunyu; Liu, Jingyi; Su, Jiaji; Liu, Ju; Cao, Changyong; Yuan, Hongyan
Abstract: Soft robots have attracted increasing attention due to their excellent versatility and broad applications. In this article, we present a minimally designed soft crawling robot (SCR) capable of robust locomotion in unstructured pipes with various geometric/material properties and surface topology. In particular, the SCR can squeeze through narrow pipes smaller than its cross section and propel robustly in spiked pipes. The gait pattern and locomotion mechanism of this robot are experimentally investigated and analysed by the finite element analysis, revealing that the resultant forward frictional force is generated due to the asymmetric mechanical properties along the length direction of the robot. The proposed simple yet working SCR could inspire novel designs and applications of soft robots in unstructured narrow canals such as large intestines or industrial pipelines.